Creación de un centro de abasto en la ciudad de Santa Rosa. - Mocha Vera, Jose Michael (My University, 2020)
Since the population of the canton has to move to the city of Machala, constantly to stock up on basic necessities, it is essential to start the creation of a wholesale supply center for products that guarantee the inhabitants of the Santa Rosa canton to have a variety , quality and direct price; that allow distribution to the current market and local stores, in order to stock up normally and can always have stock of merchandise and thus supply these micro-entrepreneurs, allowing the population and merchants to have a wholesale center that distributes consumer products, allowing with this to raise the economy of the canton; the supply of transactions will be oriented towards direct purchases from knowledgeable suppliers, in order to obtain the best prices taking into account quality standards. Entrepreneurship projects have been made a necessity by humans. We say that self-employment and the creation of new areas of employment have been fundamental to contribute to the economic development of many countries; Currently, the designated health emergency due to the pandemic has prompted the unemployed to work in the commercial system of basic necessities in the cantons of the Province of El Oro and especially in the city of Santa Rosa; Due to this event, the problem of how an enterprise such as the Creation of a Supply Center can generate commercial growth in the city of Santa Rosa was born. Also in the legal framework, this type of commercial project has all the support of the environmental authorities in order to reach households with food sustainability; currently the commercial market for basic necessities has a high precedent in demand in recent years; However, it has been necessary to request the Gad Municipal de Santa Rosa for the free fair area so that wholesale suppliers arrive one day before the commercialization of the products, which has caused a decrease in the arrival of product that can be invested in the local it is properly for a wholesale supply every 7 days a week; The market for products such as food, vegetables, dairy and meat in the Province of El Oro has a high percentage of consumption and that the Supply Center can be located as a free but more sophisticated fair and with direct prices for Santa Rosa which would be a great advantage for the retail sector since it would be located in the heart of the Province and could benefit the southern part, the upper part and the large populated cantons such as Pasaje Machala and El Guabo, which are 20 minutes away. In order to carry out this research, it has been planned as a general objective to develop an entrepreneurship plan for the creation of a Supply Center to promote a wholesale product market through the quantitative and qualitative analysis of feasibility; The method taken has been specific, through the use of the inductive-deductive reasoning process, valued in the bibliographic review, survey and unstructured direct observation, it has been confirmed that the creation of a supply center, which uses an innovative business system Through the contracting of a virtual platform, it is favorable in the commercial field after carrying out a technical analysis of the location of the supply center, on the financial side, the operational, NPV, IRR and cost / benefit status were analyzed, use of resources, we analyze the social and environmental model to dispose of product waste and evaluate the commercial impact to be generated in the city of Santa Rosa and nearby cantons in the context of 2020. It culminates that the entrepreneurial plan is aimed at building a wholesale supply center that benefits the commercial sector and the consumer at considerable cost prices, not with the desire to compete but to serve the population. It is recommended to implement youth financing projects, promote entrepreneurial talent and bring together the different branches of creational science. This document has four remotes designated to identify the wholesale sector, carry out the organizational model, know the business method and execute a commercial feasibility pattern. The bibliography is also presented, which is made up of official articles from scientific journals and national sources, and the annexes where the carrying out of the research in its different stages is presented with conviction.
Dado que la población del cantón tiene que trasladarse a la ciudad de Machala, constantemente para abastecerse de productos de primera necesidad, se hace prescindible emprender la creación de un centro de abasto mayorista de productos que garanticen a los habitantes del cantón Santa Rosa contar con variedad, calidad y precio directo; que permitan distribuir al mercado actual y tiendas de la localidad, con la finalidad de abastecerse con normalidad y puedan siempre contar con stock de mercadería y así abastecer a estos microempresarios, permitiendo que la población y comerciantes cuenten con un centro mayorista que distribuya productos de consumo, permitiendo con esto elevar la economía del cantón; el abastecimiento de transacciones se orientará a compras directas a proveedores entendidos, con el fin de conseguir los mejores precios tomando en cuenta normas de calidad. Los proyectos de emprendimiento han sido convertidos en una necesidad por los humanos, decimos que el autoempleo y la creación de nuevas áreas de empleo han sido fundamental para aportar en el desarrollo económico de muchos países; en la actualidad la emergencia sanitaria designada a causa de la pandemia ha impulsado al desempleado a laborar en el sistema comercial de productos de primera necesidad en los cantones de la Provincia de El Oro y en especial en la ciudad de Santa Rosa; por este suceso ha nacido la problemática de como un emprendimiento como es la Creación de un Centro de abasto puede generar crecimiento comercial en la ciudad de Santa Rosa. También en el marco legal este tipo de proyecto comercial cuenta con todo el apoyo de las autoridades en lo ambiental para poder llegar con la sostenibilidad alimenticia a los hogares; actualmente el mercado comercial de productos de primera necesidad tiene un precedente alto en demanda en los últimos años; sin embargo, se ha tenido que solicitar al Gad Municipal de Santa Rosa el área de la feria libre para que los abastecedores mayoristas lleguen un día antes de la comercialización de los productos que ha provocado disminuir la llegada de producto que se puede invertir que el local sea propiamente para un abasto Mayorista todos los 7 días de la semana; el mercado de productos como es víveres, verduras, lácteos y cárnicos en la Provincia de El Oro tiene un alto porcentaje de consumo y que el Centro de abasto se puede ubicar como una feria libre pero más sofisticada y con precios directos para Santa Rosa que sería una gran ventaja para el sector minorista ya que se ubicaría en el corazón de la Provincia y podrían beneficiarse la parte sur, la parte alta y los grandes cantones en población como Pasaje Machala y El Guabo que están a 20 minutos de distancia. Para poder realizar esta investigación se ha planificado como objetivo general desarrollar un plan de emprendimiento para la creación de un Centro de Abasto para impulsar un mercado de productos mayorista mediante el análisis cuantitativo y cualitativo de factibilidad; el método tomado ha sido especifico, a través del uso del proceso de razonamiento inductivo-deductivo, valorada en la revisión bibliográfica, encuesta y observación directa no estructurada se ha confirmado que la creación de un centro de abasto, que utiliza un sistema de negocio innovador a través de la contratación de una plataforma virtual, es favorable en el ámbito comercial tras realizar un análisis técnico de la ubicación del centro de abasto, en el lado financiero se analizó lo operativo, el VAN, TIR y el estado de costo/beneficio, uso de recursos, analizamos el modelo social, ambiental para desechar los residuos de los productos y evaluamos el impacto comercial que generar en la ciudad de Santa Rosa y cantones cercanos en el contexto del año 2020. Se culmina que el plan de emprendimiento está dirigido en construir un Centro de Abasto mayorista que beneficie al sector comercial y al consumidor en precios de costos considerables no con el afán de competir si no de servir a la población. Se recomienda implementar proyectos de financiamiento juveniles, promocionar el talento emprendedor y juntar las diferentes ramas de la ciencia creacional. Este documento tiene cuatro remotos designados a identificar el sector mayorista, efectuar el modelo organizacional, conocer el método del negocio y ejecutar un patrón de factibilidad comercial. También se presenta la bibliografía que está conformada por artículos oficiales de revistas científicas y fuentes nacionales, y los anexos donde se presenta con convicción la realización de la investigación en sus distintas etapas.
Keywords: EMPRENDIMIENTO; MERCADO; PRODUCTOS; ESTUDIO DE FACTIBILIDAD; TECNOLOGÍA DIGITAL